DISORDERS OF SEX DIFFERENTIATION: EVALUATION AND MANAGEMENT, A DILEMMA - Jabeen, Sadaqat; Faisal, Mahnaz; Nisar, Maleeha (Journal of Ayub Medical College Abbottabad, 2019)
The term intersex used in the past has been replaced by Disorders of Sex Differentiation. In this condition the development of chromosomal, gonadal or anatomical sex is atypical. This problem creates anxiety to the parents and a challenge for attending doctor. The problems faced by the individual are sexual, reproductive, sex of raring, placement in the society and psychological impact. The optimal management of the patient should be individualized by multidisciplinary team. Three cases of Disorders of Sex Differentiation (DSD) are presented with different causes and presentations. Two cases carrying XY karyotype pattern, while one case was of XX. The diagnosis of swyers syndrome, 5 alpha reductase deficiency and congenital adrenal hyperplasia was made on the basis of genital tract development, hormonal analysis and karyotyping. The strange feature which was common in all these cases was the wish of patients as well as family members to adopt sex of raring as male. Keywords: Disorder of sexual development; intersex gonadal dysgenesis; Awyers syndrome; congenital adrenal hyperplasia; 5 alpha reductase deficiency